2021
DOI: 10.1590/s1678-9946202163009
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of the probiotic Lactobacillus acidophilus ATCC 4356 in BALB/c mice infected with Toxocara canis

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution License.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
(56 reference statements)
2
5
0
Order By: Relevance
“…However, the suppression found in previous studies was not observed in the two groups evaluated here (G2 and G3), which kept the transcription of this interleukin at baseline levels. A similar result was observed in another study, in which IFN-γ was maintained at baseline during T. canis infection (Cadore et al, 2021), in that study IL-12 was not evaluated, but considering that IFN-γ production by natural killer cells is stimulated by IL-12 (Airoldi et al, 2002), probably both were at baseline levels.…”
Section: Treatment With Csa Increases the Recovery Of T Canis Larvaesupporting
confidence: 78%
“…However, the suppression found in previous studies was not observed in the two groups evaluated here (G2 and G3), which kept the transcription of this interleukin at baseline levels. A similar result was observed in another study, in which IFN-γ was maintained at baseline during T. canis infection (Cadore et al, 2021), in that study IL-12 was not evaluated, but considering that IFN-γ production by natural killer cells is stimulated by IL-12 (Airoldi et al, 2002), probably both were at baseline levels.…”
Section: Treatment With Csa Increases the Recovery Of T Canis Larvaesupporting
confidence: 78%
“…(52% reduction for L. rhamnosus and 58% for L. acidophilus). As previously found for S. boulardii, L. rhamnosus and L. acidophilus displayed their effects in vivo but did not exert a direct effect on the parasite in vitro, demonstrating once more that the interaction between the host and these bacteria is of paramount importance for the protective effects (de Avila et al, 2012;Walcher et al, 2018;Cadore et al, 2021).…”
Section: Toxocara Sppsupporting
confidence: 68%
“…Whereas the antibacterial and antifungal activity [33,34] of L. acidophilus has been well illustrated, the antiparasitic properties of L. acidophilus has been less studied. L. acidophilus in combination with other probiotics is beneficial in the prevention and treatment of Giardia lamblia infection in mice [35], Toxocara canis [36], Trichinella spiralis [37] and Cryptosporidium parvum [38]. In a recent work, we have demonstrated that L. acidophilus is detrimental to E. histolytica but the amebicide mechanism was unknown [19].…”
Section: Discussionmentioning
confidence: 99%